(untitled) (International Journal of Food and Nutritional Sciences, 2022)
“Personnel management is a part of management purpose which is primarily worried with the human relationship within the organization. Its objective is preservation of those relationships on a basis of consideration of the well being individual, enables all those occupied in the undertaking to make their maximum contribution to the effective of that undertaking.” For making an organization successful, not only material, land, machine is essential but also Personnel Management and effective use of manpower is essential. “Personnel management undertakes the process of planning and directing the application, development and utilization of human resource in employment.” Such process leads a role of organizational goals and effective use of manpower in it. In this way of achievement of organizational objective, employee satisfaction , for improving quality of product or services and for effective use of all inputs, management needs to give due substance to Personnel Management and this research is directed towards analytical study of Personnel Management and its functions in TNSTC , Vizhuppuram District.